Y90 Radiation Segmentectomy versus Microwave Ablation for Hepatocellular Carcinoma in Locations Suboptimal for Percutaneous Ablation - Olivia Kola; John A. Cieslak; Nirav Chauhan; Priya Gupta; Pratik Shukla; Abhishek Kumar (The Arab Journal of Interventional Radiology)
Purpose The purpose of our study was to evaluate outcomes following percutaneous microwave ablation (MWA) versus yttrium-90 (Y90) radiation segmentectomy (RS) for tumors in suboptimal locations for ablation.